Analysis of the Reasons for Visits to the Dentist in Young Children During the Covid-19 Pandemic - Yusupov Sharif Abror ugli (Zien Journals, 2022)
COVID-19 pandemic significantly affected dentistry due to high coronavirus infectivity and dangerous consequences. Special recommendations were developed for dentists to limit the infection of staff and patients. to study the reasons for children visiting dental clinics during COVID-19 pandemic and give the characteristics of the patients and provided dental treatment. The cross-sectional study was conducted in four dental clinics, which worked for dental emergency in the cities of Volgograd and Volzhky during the peak of COVID-19 pandemic. The data about 166 paediatric dental patients aged 1-17 years were collected. The reasons for children’s dental visits, age and behavior of the children, the tooth types, and the types of provided treatment were analyzed. The children’s behavior was assessed according to Frankl’s Behavior Rating Scale. Proportions (%), 95% Confidence Interval (CI), mean-value with standard error (M±m) were calculated. The differences were assessed by Pierson’s Chi-square test at p-value 0.05. Microsoft-office Excel-2019 programs were used for the statistic analysis. The majority (98.8%, 95% CI 95.7-99.7%) of the children visited dental clinics due to acute toothache. The primary teeth needed urgent treatment significantly more often than permanent teeth: 83.7% (95% CI 77.8-88.3%) and 16.3% (95% CI 11.7-22.2%) respectively, x2 = 172.171, p < 0.0001. Among the primary teeth the most affected ones were the first and second molars, among the permanent teeth – the first molar. The common reasons for urgent dental treatment in children were caries consequences: apical periodontitis (51.6%, 95% CI 44.5-58.6) or pulpitis (35.3%, 95% CI 28.8-42.3). The other reasons were dental trauma, caries, periostitis, physiological primary tooth mobility. Acute pain in the primary teeth was caused mainly by apical periodontitis, in the permanent teeth by pulpitis. The applied treatment methods were aimed at limiting the use of aerosol generating procedures, reducing the duration of the treatment and preventing the patients’ hospitalization. Almost all the primary teeth with apical periodontitis were extracted; the number of extracted and endodontically treated permanent teeth was approximately equal. The current methods of pulpitis treatment (pulp capping, pulpotomy and pulpectomy) were applied along with the pulp necrotizing agent use. Many (39.7%, 95% CI 32.6-47.4%) children demonstrated negative behavior. Behavior management techniques were used, including tell-show-do (54.5%, 95% CI 42.6-66.0%), sedation (3.0%, 95% CI – 0.8-10.4%), general anesthesia (3.0%, 95% CI – 0.8-10.4%), passive restraint (39.4%, 95% CI 28.5-51.4%). In the limitation of this study we can conclude that COVID-19 pandemic changed the profile of paediatric dental patients and dentist’s treatment options. In 1-17-year-old children the main reason for an emergency dental visit was acute dental pain due to caries consequences. The primary teeth needed urgent dental treatment significantly more often than the permanent teeth. The children often demonstrated negative behavior and required behavior management. The applied treatment methods were aimed at limiting the use of aerosol generating procedures, decreasing the duration of the treatment and avoiding the patients’ hospitalization.
Keywords: COVID-19; dentistry; children; emergency